2015
DOI: 10.1038/sj.bdj.2015.817
|View full text |Cite
|
Sign up to set email alerts
|

Understanding emotionally relevant situations in primary care dental practice: 1. Clinical situations and emotional responses

Abstract: Background and Aims: The stressful nature of dental practice is well established. Much less information is available on the coping strategies used by dentists and the emotions which underlie the stressful experience. Previous research has been almost exclusively questionnaire-based, limiting the range of emotions explored. This study used qualitative methods to explore the full extent of emotions and coping strategies associated with stressful events in primary dental practice. Method: Semi-structured intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 44 publications
1
33
0
1
Order By: Relevance
“…Has been accepted as a stressor 8;25 but the previous study 20 found that perfectionism was a 'double-edge sword' functioning as a motivator for high clinical standards and a A deeper exploration of the dichotomy was important to inform the coping skills package.…”
Section: The Impact Of Perfectionismmentioning
confidence: 99%
See 1 more Smart Citation
“…Has been accepted as a stressor 8;25 but the previous study 20 found that perfectionism was a 'double-edge sword' functioning as a motivator for high clinical standards and a A deeper exploration of the dichotomy was important to inform the coping skills package.…”
Section: The Impact Of Perfectionismmentioning
confidence: 99%
“…13 Previously reported qualitative research [14][15][16] has explored dentists' stressful situations, accompanying emotions and the coping strategies used. The authors intended to use these data to inform the design of a self-help, stress management package for dentists.…”
Section: Introductionmentioning
confidence: 99%
“…As previously described, 1 many participating dentists referred to 'stress' as the major emotion they experienced at work. However, 'stress' is the perception of an overwhelming underlying emotion.…”
Section: Introductionmentioning
confidence: 99%
“…10 The possibility of emotional vicious circles was previously reported by dentists. 1 An alternative model of coping is given by Power 11 who emphasises the importance of the functionality of coping strategies over an analysis of the behavioural or emotional focus. Strategies can be internal to the self, as in trying to slow one's breathing rate or external, such as ensuring one writes thorough, contemporaneous notes.…”
Section: (Figure 1)mentioning
confidence: 99%
See 1 more Smart Citation